In vitro anti-blastocystis effects of garlic, ginger and betel leaf extract on blastocystis sp. Obtained from cattle - Mohammad, Mardhiah; Kamaruddin, Sitie Kasmadiana (2018)
Blastocystis is a protozoan parasite that can cause gastrointestinal disorder in human and animal. It has a worldwide distribution with high genetic diversity and can be classified into subtypes. To date, 17 subtypes of Blastocystissp. have been reported with subtype 3 and 10 predominantly found in human and cattle respectively. Metronidazole (MTZ) is the main therapy for blastocystosis. However, reports of hazardous side effects and treatment failures suggests potential development of drug resistance, hence incur need for alternative therapeutics. Thus, this study was aim to investigate in vitro effects of garlic, ginger and betel leaf extract against subtype 10 of Blastocystis sp. isolated from cattle. Fecal samples positive for Blastocystis were subjected to genotypic subtyping using PCR sequencing and also processed for culture. Cultured parasites were tested with 0.01 and 0.1 mg/ml concentration of the herbs extract and MTZ. The effects were monitored daily and growth inhibition was calculated after 48 hours. All three herbs showed statistically significant (p<0.05) in vitro growth inhibition of Blastocystis compared to the untreated control in both concentrations. In treatment of 0.01mg/ml, ginger has significantly (p<0.001) lowered the number of parasites (5.63 x105±1.68) with reduction rate of 95.33%. Whereas, the number of parasites after treatment with garlic (10.13x105±3.71) and betel leaf (21x105±6.4) were lowered with reduction rates of 91.60% and 82.57% respectively (p<0.05). The number of parasites (0.38x105±0.7) was significantly (p<0.001) lowered after treatment with MTZ and the reduction rate after 48 hours was 99.68%. Treatment of 0.1mg/ml improved these results indicated that the effect was concentration dependent. These findings revealed the potential therapeutic effects of garlic, ginger and betel leaf as alternatives against blastocystosis. Nevertheless, ginger was the best among the three herbs.